No second Eden : poems - Cassity, Turner (Swallow Press/Ohio University Press, 2002)
If you think that Turner Cassity has mellowed or slowed down since the 1998 release of his selected poems, The Destructive Element, think again. In No Second Eden Cassity is back more Swiftian than ever. Among the targets reduced to ruin are countertenors, parole boards, the French Symbolists, calendar reformers, the Yale Divinity School, and the cult of Elvis. Without turning a blind eye, he even extends a toast to Wernher von Braun. Surprisingly, there is a poem about the Mississippi in which Cassity grew up. Unsurprisingly, it is a vision quite unlike others of that state. Its chilly and.